2005
DOI: 10.1007/s11199-005-7140-x
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Validation of the Genderism and Transphobia Scale

Abstract: A series of three studies were conducted to develop and validate a scale to measure violence, harassment, and discrimination toward cross-dressers, transgenderists, and transsexuals. In Study 1, we developed the Genderism and Transphobia Scale (GTS). In Study 2, we established the GTS's ability to predict parents' reactions to either a gender conforming or a gender non-conforming boy or girl. Correlations between the GTS and scales that assess homophobia and gender role ideologies suggest convergent validity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
471
8
14

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 460 publications
(531 citation statements)
references
References 20 publications
38
471
8
14
Order By: Relevance
“…This may be because the latter is rather blunt in the wording of its items, and the former includes both attitudinal and knowledge items. The issue of measures focusing on attitudes towards trans people being too blunt has also been raised by Ali et al (2016), whose participants suggested that the Genderism and Transphobia Scale (Hill & Willoughby, 2005) uses "unnecessarily inflammatory language" (p. 271). Concerns about the Genderism and Transphobia Scale led Riggs, Webber and Fell (2012) to adapt the scale in ways similar to the adaptions applied to the CATTS and ATTIS in the present study, producing factors that were argued to be relevant to the Australian context.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because the latter is rather blunt in the wording of its items, and the former includes both attitudinal and knowledge items. The issue of measures focusing on attitudes towards trans people being too blunt has also been raised by Ali et al (2016), whose participants suggested that the Genderism and Transphobia Scale (Hill & Willoughby, 2005) uses "unnecessarily inflammatory language" (p. 271). Concerns about the Genderism and Transphobia Scale led Riggs, Webber and Fell (2012) to adapt the scale in ways similar to the adaptions applied to the CATTS and ATTIS in the present study, producing factors that were argued to be relevant to the Australian context.…”
Section: Discussionmentioning
confidence: 99%
“…As alluded to above, researchers in the field consistently argue that negative attitudes toward homosexuality may be a reflection of negative perceptions of gender norm violations, in general. In addition, previous research (Hill & Willoughby, 2005) suggests that attitudes toward transsexuality and homosexuality are related. Therefore, it seems that the potential moderating effect of general attitudes toward transsexuality and homosexuality is a worthy consideration when examining perceptions of a specific transsexual.…”
Section: Gender Differences In Attitudes Toward Transsexualsmentioning
confidence: 96%
“…In addition, transphobia, attitudes toward homosexuality, gender-role beliefs, and gender-role selfconcept were proposed as moderating variables. The methodology involved the use of vignettes and photographs designed to elicit attitudinal ratings toward a transsexual vignette character, as well as previously validated measures of the stated moderating variables including the Genderism and Transphobia Scale (GTS) (Hill & Willoughby, 2005), the Kite Homosexuality Attitude Scale (Kite & Deaux, 1986), the Hypergender Ideology Scale (HGIS) (Hamburger, Hogben, McGowan, & Dawson, 1996), and the Personal Attributes Questionnaire (PAQ) (Spence, Helmreich, & Stapp, 1974). The attitudinal ratings of the transsexual person were derived from questions similar to those used in comparable research (Moulton & Adams-Price, 1997) and assessed perceived attractiveness, general perception, and emotional health of the transsexual character.…”
Section: Summary Of Studymentioning
confidence: 99%
See 2 more Smart Citations